If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2) + ln(x + -2) = ln(21) Reorder the terms: (2 + x) + ln(x + -2) = ln(21) Remove parenthesis around (2 + x) 2 + x + ln(x + -2) = ln(21) Reorder the terms: 2 + x + ln(-2 + x) = ln(21) 2 + x + (-2 * ln + x * ln) = ln(21) 2 + x + (-2ln + lnx) = ln(21) Reorder the terms: 2 + -2ln + lnx + x = ln(21) Reorder the terms for easier multiplication: 2 + -2ln + lnx + x = 21ln Solving 2 + -2ln + lnx + x = 21ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-21ln' to each side of the equation. 2 + -2ln + lnx + -21ln + x = 21ln + -21ln Reorder the terms: 2 + -2ln + -21ln + lnx + x = 21ln + -21ln Combine like terms: -2ln + -21ln = -23ln 2 + -23ln + lnx + x = 21ln + -21ln Combine like terms: 21ln + -21ln = 0 2 + -23ln + lnx + x = 0 Add '-2' to each side of the equation. 2 + -23ln + lnx + -2 + x = 0 + -2 Reorder the terms: 2 + -2 + -23ln + lnx + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -23ln + lnx + x = 0 + -2 -23ln + lnx + x = 0 + -2 Combine like terms: 0 + -2 = -2 -23ln + lnx + x = -2 Add '-1x' to each side of the equation. -23ln + lnx + x + -1x = -2 + -1x Combine like terms: x + -1x = 0 -23ln + lnx + 0 = -2 + -1x -23ln + lnx = -2 + -1x Reorder the terms: 2 + -23ln + lnx + x = -2 + -1x + 2 + x Reorder the terms: 2 + -23ln + lnx + x = -2 + 2 + -1x + x Combine like terms: -2 + 2 = 0 2 + -23ln + lnx + x = 0 + -1x + x 2 + -23ln + lnx + x = -1x + x Combine like terms: -1x + x = 0 2 + -23ln + lnx + x = 0 The solution to this equation could not be determined.
| 3d=d-7=25/4 | | 3x-x-x+2=13 | | -(2x-3)=-6 | | 6x-3.3=4x-8.3 | | 1.8*4.8= | | 4+6j+10=20+6(5) | | 1/2secx=1 | | f(-2)=2x^3+3x^2-12x+7 | | 7y=6x+2 | | 7=21m | | 8+6=5+2 | | 12f+1-4=-3(1)+5(1)-11 | | (x+6)=25.1 | | 5t-4(10)=9 | | x^2-10x+6=-4 | | 12x+42= | | q(4q+1)=0 | | 12*k=20 | | 4-(1/x^2)0 | | 12+1x=.5x | | 86+26=256-9x | | 2/3*2/3*2/3*2/3*2/3 | | 7x-11=5(x+2)+2x-1 | | 47*0.25=k | | 2/3)^5 | | 7n=6n-5 | | n=6n-5 | | 3(z+1)=6 | | x^4-3x^5=0 | | -8/3(y-12)-1/9y= | | (2x-1)=3x-19 | | 10+3y=28 |